Clinical importance of Familial Pancreatic Cancer Registry in Japan: a report from kick‐off meeting at International Symposium on Pancreas Cancer 2012. Issue 6 (August 2013) - Wada, Keita; Takaori, Kyoichi; Traverso, L. William; Hruban, Ralph H.; Furukawa, Toru; Brentnall, Teresa A.; Hatori, Takashi; Sano, Keiji; Takada, Tadahiro; Majima, Yoshiyuki; Shimosegawa, Tooru
Abstract Pancreatic cancer is still a highly lethal disease with a 5‐year survival rate of approximately 5 %. Early detection offers one of the best hopes for improving survival. Previous cohort studies and case—control studies showed that 4—10 % of pancreatic cancers have a hereditary basis, and individuals with a family history have an increased risk of developing pancreatic and extra‐pancreatic malignancies. Since individuals with a family history of pancreatic cancer and those with a known genetic syndrome that predisposes to pancreatic cancer will be the first to benefit from early detection tests as they become available, familial pancreatic cancer (FPC) registries have been established in the US and Europe, but not yet in Japan. Such registries form the basis for epidemiological studies, clinical trials, and basic research on familial pancreatic cancer. There is a need for FPC registries in Japan as cancer risk varies among different populations and discoveries made in Western populations may not translate to the Japanese population. These registries in Japan will align with ongoing international efforts and add to a better understanding of the natural history, risk factors, screening strategies, and responsible genes, for improving survival of this dismal disease.